2007
DOI: 10.1007/s00068-007-6138-1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Quality Management of Apallic Syndrome / Vegetative State

Abstract: Management of AS aims at the social reintegration of patients or has to guarantee humanistic active nursing if treatment fails. Outcome depends on the cause and duration of AS/VS as well as patient's age. There is no single AS/VS specific laboratory investigation, no specific regimen or stimulating intervention to be recommended for improving higher cerebral functioning. Quality management requires at least 3 years of advanced training and permanent education to gain approval of qualification for AS/VS treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 130 publications
(209 reference statements)
0
9
0
6
Order By: Relevance
“…Coma vigil was discarded because the term is a contradiction in terminis, given that coma patients by definition never open their eyes. Apallic syndrome was also rejected, as recent evidence has shown that these patients are not a-pallic (meaning without a cortex or pallium) [35], but classically show preserved albeit disconnected islands of residual (merely primary) cortical functioning [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Coma vigil was discarded because the term is a contradiction in terminis, given that coma patients by definition never open their eyes. Apallic syndrome was also rejected, as recent evidence has shown that these patients are not a-pallic (meaning without a cortex or pallium) [35], but classically show preserved albeit disconnected islands of residual (merely primary) cortical functioning [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Cur rently the methods of functional neurosurgery and, primarily, neuromodulation, have found application in the complex treatment of Parkinsonism, various forms of torsion dystonia, infantile cerebral paralysis, spastic syndromes, epilepsy, chronic pain syndromes of neurogenic and visceral genesis, severe forms of obsessive compulsory disorders, depression, and other diseases [43]. The possibilities of brain neuromodula tion in long lasting unconscious states, including the persistent vegetative condition and the condition of minimal consciousness after a severe brain trauma, continue to be investigated [4,16,18].…”
Section: Current Technologies and Basic Research In Neurosurgerymentioning
confidence: 99%
“…During examination in modes T2 FLAIR(1,3) and SWAN (2) on the fourth day after the trauma, lesions were identified at the level of the mesolobus, pons, and midbrain; during examination on the 33rd day (4, 6, T2 FLAIR; 5, the map of fractional anisotropy in the saggital plane) and after four months (7, 9, T2 FLAIR; 8, the map of fractional anisot ropy), atrophic changes in the cerebral hemispheres, pons, and mesolobus; (b) the dynamics of MR tractography data. Exami nation on the fourth day (1, 2) determined the partial absence of visualization of fibers on the front third of the mesolobus, the corticospinal tracts being relatively symmetrical; examination on the 33rd day(3,4) visualizes only individual ascending fibers in the middle part, as well as in the genu and splenium of the mesolobus; the asymmetry of corticospinal tracts (CSTs), the thinning of fibers on the left; examination four months after the trauma (5, 6) revealed only individual fibers in the area of the genu and splenium of the mesolobus, as well as severe asymmetric thinning of the CSTs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical guidelines and scales like the Glasgow Coma Scale (GCS) or the JFK Coma Recovery Scale–revised (JFK CRS-r) represent the gold standard in describing the clinical state of these patients [4-6]. With these clinical methods, diagnoses are mostly based on observable motor behavior.…”
Section: Introductionmentioning
confidence: 99%